Practical Management of ANCA-Associated Vasculitis: A Clinician’s Perspective - Hannah L. Stacey; Lucy Francis; Rona M. Smith; Rachel B. Jones (Glomerular Diseases)
Background: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis can be a life-threatening condition, characterized by necrotizing inflammation of small blood vessels. Major organ involvement, most commonly kidney and lung disease, is associated with significant morbidity and mortality. Intensive early immunosuppressive therapy is the cornerstone of management and has transformed ANCA-associated vasculitis (AAV) into a chronic relapsing condition. Remission induction with tapering glucocorticoids in combination with cyclophosphamide or rituximab is the standard of care for severe disease. Avacopan, an oral C5aR1 antagonist, has been approved for remission induction and helps minimize glucocorticoid exposure. Plasma exchange should be considered for severe kidney or life-threatening disease. Lower dose glucocorticoid induction regimens can be used without compromising remission rates. Remission maintenance therapy is recommended, and rituximab is usually first line over azathioprine. Mycophenolate mofetil (MMF) or methotrexate with low-dose glucocorticoids are third-line options. Immunosuppression-associated infection risk remains a concern, both during acute presentations and in the long term, highlighted by the impact of rituximab on humoral immunity and vaccine response during the COVID-19 pandemic. There remains an ongoing need for therapies that induce rapid remission and optimize kidney recovery while minimizing infection risk. Clinical trials are evaluating newer therapeutic options. Due to increasing treatment options, management should be individualized, balancing effective immunosuppression against comorbidities and frailty. Summary: This review focuses on the treatment decision pathways for clinicians and patients in the management of severe AAV (granulomatosis with polyangiitis and microscopic polyangiitis). Key clinical trials, predictors of outcome, novel therapeutics, and practical steps to mitigate infection risk are discussed. Key Messages: Immunosuppression regimens have been refined due to emerging evidence from clinical trials. Rituximab, avacopan, and reduced-dose glucocorticoid schedules have been the focus of recent studies. Infections and immunosuppression-induced immunodeficiency must be considered when determining individualized treatment. Background: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis can be a life-threatening condition, characterized by necrotizing inflammation of small blood vessels. Major organ involvement, most commonly kidney and lung disease, is associated with significant morbidity and mortality. Intensive early immunosuppressive therapy is the cornerstone of management and has transformed ANCA-associated vasculitis (AAV) into a chronic relapsing condition. Remission induction with tapering glucocorticoids in combination with cyclophosphamide or rituximab is the standard of care for severe disease. Avacopan, an oral C5aR1 antagonist, has been approved for remission induction and helps minimize glucocorticoid exposure. Plasma exchange should be considered for severe kidney or life-threatening disease. Lower dose glucocorticoid induction regimens can be used without compromising remission rates. Remission maintenance therapy is recommended, and rituximab is usually first line over azathioprine. Mycophenolate mofetil (MMF) or methotrexate with low-dose glucocorticoids are third-line options. Immunosuppression-associated infection risk remains a concern, both during acute presentations and in the long term, highlighted by the impact of rituximab on humoral immunity and vaccine response during the COVID-19 pandemic. There remains an ongoing need for therapies that induce rapid remission and optimize kidney recovery while minimizing infection risk. Clinical trials are evaluating newer therapeutic options. Due to increasing treatment options, management should be individualized, balancing effective immunosuppression against comorbidities and frailty. Summary: This review focuses on the treatment decision pathways for clinicians and patients in the management of severe AAV (granulomatosis with polyangiitis and microscopic polyangiitis). Key clinical trials, predictors of outcome, novel therapeutics, and practical steps to mitigate infection risk are discussed. Key Messages: Immunosuppression regimens have been refined due to emerging evidence from clinical trials. Rituximab, avacopan, and reduced-dose glucocorticoid schedules have been the focus of recent studies. Infections and immunosuppression-induced immunodeficiency must be considered when determining individualized treatment.